Quality of Service As an Element Improving Customer Satisfaction Bank Mandiri Syariah Regional III Jakarta - Dickdick Sodikin; Abdul Muslim (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study connects service quality with customer satisfaction at Bank Mandiri Syariah Regional Operasional 3 Jakarta. The results of the study concluded that the service received by the customer was in accordance with his expectations even though it was still elements of the service that needed to be improved such as the ability to understand the needs of its customers. From the results of the analysis show a positive influence on service quality on strong and significant customer satisfaction. In connection with the research conducted, it is recommended that management complete facilities to support the improvement of service quality so that customer satisfaction increases so that it becomes a loyal customer.Â